Sovereign Wealth Funds and Financial Stability-An Event Study Analysis - Hesse, Heiko (IMF Working Papers; Working Paper ;, 2009)
This paper examines financial stability issues that arise from the increased presence of sovereign wealth funds (SWFs) in global financial markets by assessing whether and how stock markets react to the announcements of investments and divestments to firms by SWFs using an event study approach. Based on 166 publicly traceable events collected on investments and divestments by major SWFs during the period from 1990 to 2009, the paper evaluates the short-term financial impact of SWFs on selected public equity markets in which they invest. The impact is analyzed on different sectors (financial and nonfinancial), actions (buy and sell), market types (developed and emerging markets), and level of corporate governance (high and low score). Results, based on these 166 events, show that there was no significant destabilizing effect of SWFs on equity markets, which is consistent with anecdotal evidence.